STUDI KASUS PENGALAMAN DAN TANTANGAN REMAJA HOMOSEKSUAL DI JAKARTA - Noryck Pradana; Rahmawati Rahmawati; Lenny Wahyuningsih (Jurnal Penelitian Bimbingan dan Konseling, 2023)
This research is motivated by the problem of homosexual teenagers in the city of Jakarta. The aim of the research is to find out movements in the city of Jakarta, find out the factors that cause homosexual behavior, and find out the experiences and challenges of homosexual teenagers in Jakarta. This research uses a qualitative approach with a case study research method. Informants were taken using a purposive method. The setting of this research was carried out in the city of Jakarta. This data collection method was carried out using in-depth interviews. The data validity test was carried out using the source triangulation method. The data analysis technique used is an interactive model consisting of data reduction, data display, and drawing conclusions. The results of the research show that homosexuals in the city of Jakarta are free in their actions and have begun to speak out through parades in certain places. Factors that cause homosexuality are based on the friendship environment, the influence of hormones, and problems in the family. The experiences and challenges received include experiencing rejection from the family and bad views from the community.Keywords: homosexual, factors, experience..